2008
DOI: 10.1152/ajpheart.00115.2008
|View full text |Cite
|
Sign up to set email alerts
|

p75 neurotrophin receptor regulates agonist-induced pulmonary vasoconstriction

Abstract: JXJ. p75 neurotrophin receptor regulates agonist-induced pulmonary vasoconstriction. Am J Physiol Heart Circ Physiol 295: H1529-H1538, 2008. First published August 8, 2008 doi:10.1152/ajpheart.00115.2008.-A member of the TNF receptor family, the p75 neurotrophin receptor (p75 NTR ) has been previously shown to play a role in the regulation of fibrin deposition in the lung. However, the role of p75 NTR in the regulation of pulmonary vascular tone in the lung is unknown. In the present study, we evaluated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…There is now some evidence that NT signaling may be important in the control of vascular structure and function [37,8084]. In extrapulmonary branches of the human pulmonary artery, immunocytochemical studies show that NGF, BDNF and NT3 are present at comparable levels, particularly in the intima as well as the adventitia (with some reactivity in the inner layer of the smooth muscle media) [84].…”
Section: Neurotrophins In the Lungmentioning
confidence: 99%
See 1 more Smart Citation
“…There is now some evidence that NT signaling may be important in the control of vascular structure and function [37,8084]. In extrapulmonary branches of the human pulmonary artery, immunocytochemical studies show that NGF, BDNF and NT3 are present at comparable levels, particularly in the intima as well as the adventitia (with some reactivity in the inner layer of the smooth muscle media) [84].…”
Section: Neurotrophins In the Lungmentioning
confidence: 99%
“…Furthermore, in human pulmonary artery rings, these NTs induce acute vasodilation that is blunted by removal of the endothelium. In mouse pulmonary arteries, the low-affinity p75NTR receptor is expressed in both the endothelium and smooth muscle [80]. Furthermore, pulmonary artery rings from p75NTR knockout mice show significantly elevated contractions in response to endothelin-1 (but not other constrictors, suggesting the involvement of specific Ca 2+ regulatory mechanisms).…”
Section: Neurotrophins In the Lungmentioning
confidence: 99%
“…Neurotrophins and their receptors are expressed on pulmonary arteries (Ricci et al, 2000a), and their expression is increased in the lung of spontaneously hypertensive rats (Ricci et al, 2004a). A role for neurotrophins in the control of the pulmonary arterial tone was recently proposed, through activation of the p75 NTR receptor (Xu et al, 2008). BDNF and NT-3 induce relaxation of porcine pulmonary arterial rings, through activation of the endothelial nitric oxide synthase (Meuchel et al, 2011).…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…Overall, these data point to a complex role of locally-produced BDNF within the PA that may detrimentally or beneficially influence arterial contractility and relaxation in a context-sensitive fashion. A single study in pulmonary artery rings from p75NTR knockout mice showed increased contractions to endothelin-1[ 64 ] suggesting a vasodilatory role for neurotrophins, however such an effect cannot be attributed to BDNF (p75NTR is activated by all neurotrophins), to TrkB, or to PASMCs. Furthermore, it is likely that long-term lack of p75NTR could have a completely different effect on vascular structure and function.…”
Section: Discussionmentioning
confidence: 99%